2014
DOI: 10.1111/cei.12320
|View full text |Cite
|
Sign up to set email alerts
|

Instructive influences of phagocytic clearance of dying cells on neutrophil extracellular trap generation

Abstract: Instructive influences of phagocytic clearance of dying cells on neutrophil extracellular trap generation OTHER ARTICLES PUBLISHED IN THIS SERIESDying autologous cells as instructors of the immune system. Clinical and Experimental Immunology 2015, 179: 1-4. Anti-dsDNA antibodies as a classification criterion and a diagnostic marker for systemic lupus erythematosus: critical remarks. Clinical and Experimental Immunology 2015, 179: 5-10. The effect of cell death in the initiation of lupus nephritis. Clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…We observed that the concurrence of necrotic cells and NETosis leads to the entrapment of the dead cells. A recent report on NETosis induced by apoptotic cells in vitro also supports the link between cell death and NETosis (49). …”
Section: Discussionmentioning
confidence: 56%
“…We observed that the concurrence of necrotic cells and NETosis leads to the entrapment of the dead cells. A recent report on NETosis induced by apoptotic cells in vitro also supports the link between cell death and NETosis (49). …”
Section: Discussionmentioning
confidence: 56%
“…45 Apoptosis has been described in inflammatory myopathies, 46,47 at least in some cases as a result of the cytotoxic action of T lymphocytes. Finally, the generation of neutrophil extracellular traps (NETs), an event strictly associated with the activation of autophagy pathway in inflammatory leukocytes 48 and modulated by the recognition of apoptotic cells, 49 has been described in the muscle upon ischemia-reperfusion injury. 50 Further studies will evaluate the relevance of NET contribution to muscle remodeling during autoimmune diseases and in homeostatic conditions.…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%
“…A variety of stimuli have been reported to induce formation of NETs, among them are bacteria, fungi, and microbial products (3, 5, 6). Other physiological stimuli include monosodium urate, immune complexes, apoptotic cells, or integrin-mediated signals at high cellular density (710). In experimental settings, chemicals with defined mechanisms of action such as phorbol-2-myristate-13-acetate (PMA) or ionomycin also induce NET formation (4).…”
Section: Introductionmentioning
confidence: 99%